ANALISIS PENENTUAN PUTUS STUDI (DROP OUT) MAHASISWA SEKOLAH PASCASARJANA UNIVERSITAS SUMATERA UTARA MENGGUNAKAN ALGORITMADATA MINING C 4.5 - DARA SAWITRI (LP2MTBM MAKARIOZ, 2019)
To determine the dropout of the study (droup out) University of Sumatera Utara graduate school students, the author tries to help determine the dropout of the study by using an algorithm in data mining, the C.4.5 algorithm. Data of University of Sumatera Utara graduate school students are processed in tabular form so that a decision tree can be obtained to be explored and then developed again. After the decision tree is obtained, data analysis is done using SPSS (Statistical Product and Service) software and RapidMine software is used to display the decision results. The results obtained are obtained a rule model that can show the relationship rules of existing variables, determine the variables that influence the determination of study dropouts at the University of Sumatera Utara graduate students and be able to predict study dropouts at the University of Sumatera Utara Postgraduate Studies ie the study drop out prediction if the GPA <3 and duration of Study> 8 and Study Load <36 SKS.